Development of a pharmacy counselling tool for parents of school-age asthma patients in the Philippines - Chua, Adson Jr. S.; Flores, Lawrence Jay C.; Pineda, Phylicia Marie T.
Pharmacy patient counselling is intended to improve the adherence to the proper regimen, maintain the quality of life, prevent the morbidity and mortality due to improper drug utilization and administration. Pediatric asthma is the most common chronic lower respiratory disease in childhood throughout the world. To prevent or control the attacks of asthma, patient education is an essential aspect of self-managed care together with the guidance of their parents in the education process. The researchers intend to provide pharmacists a validated counselling tool which is directed for parents and caregivers of pediatric asthma patients aged 6 to 11. The content and structure of the tool was developed through review of literature, nominal group technique, structured interviews and pretesting. In the pilot study, the researchers evaluated the effectiveness of the tool using a quasi-experimental pre-test post-test model measuring asthma knowledge, attitudes and practices of caregivers before and after counseling sessions wherein the tool was utilized. In general, the use of the tool was able to achieve its intended goal when used in a counseling session involving the participating caregivers. All participants subjectively find the counselling session beneficial, and the tool was able to considerably increase the knowledge of the patients regarding pediatric asthma (p=0.0422) while scores for attitude and practice have increased as well, however not significantly.
Thesis (BS Pharmacy) University of the Philippines Manila
Keywords: Pharmaceutical Services; Asthma